Armenianate expressions: Exploring the Armenian contribution to the formation of Great Imperial Traditions in the Middle Ages - Nucciotti, Michele (ARAMAZD: Armenian Journal of Near Eastern Studies, 2025)
This brief contribution is intended as a further interlocution on the theme of Armenian identity, within the long-standing dialogue I have had the pleasure and honour to share with Hamlet Petrosyan since 2010. Hamlet—with whom I have shared research, intellectual exchange, and debate, as well as countless logistical challenges related to the joint Armenian–Italian archaeological missions in Vayots Dzor and at Dvin, and in the organization of student exchange programs between Yerevan State University and the University of Florence—has represented, for me, the gateway to the culture of medieval Armenia. Our first encounter was made possible through the kind intermediation of our mutual friend Rouben Galichian, who introduced Guido Vannini and myself to Hamlet in order to begin an initial mapping of the Silk Road landscapes in Vayots Dzor. Remarkably, a video record of that very first meeting still exists, in a short documentary entitled Archaeological Tourists in Armenia, filmed by another mutual friend, Riccardo Polveroni, during our first exploratory mission in Vayots Dzor (https:// shorturl.at/wbDjl). I therefore dedicate the reflections that follow to my friend and colleague Hamlet Petrosyan, as a stimulus for our ongoing and future discussions.